Digital humanities indexed in DOAJ: An analysis of scientific publications - Silva Damasceno, Fernanda; Vieira Vitorino, Elizete (Advanced Notes in Information Science, 2023)
It presents an analysis of publications about Digital Humanities indexed in Portuguese in the Directory of Open Access Journals (DOAJ) from 2017 to 2021. A simple search was performed using the term “digital humanities” which retrieved 33 articles published in 25 open-access scientific journals. The results are presented in three sections representing three main fields of study. It was possible to conclude that publications about digital humanities have been growing and that some of those publications’ concerns are to show projects and the digital tools used on them. In addition, they mention distant reading, big data, and the COVID-19 pandemic. It was also noticed that some of the articles retrieved misinterpret what Digital Humanities is. The expansion of databases is suggested for future research on this subject, favoring even the information literacy of researchers interested in this theme.